COST AND NON-COST FACTORS: THE IMPORTANCE OF REPURCHASE INTENTION TO FACING COMPETITION IN INDONESIAN RETAIL INDUSTRY - Alfonsius, Alfonsius; Nicola, Jasmine (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
In the current situation, certain retail businesses may have encountered difficulties in developing their businesses, particularly home appliance companies. This study aims to analyze the influence of sales promotion and service quality on customer repurchase intention at Ace Hardware Putri Hijau, Medan. Developing customer repurchase intention is crucial for business continuity nowadays. Improving sales promotion and service quality performances may be beneficial since sales promotion involves incentives to stimulate customer purchases and service quality emphasizes fulfilling customer needs, which can lead to achieving the company’s objectives. Questionnaires were distributed to 100 Ace Hardware Putri Hijau, Medan respondents using a purposive sampling method. The data is analyzed based on multiple linear regression analysis. Based on the findings, it is concluded that sales promotion significantly influences customer repurchase intention, and service quality significantly influences customer repurchase intention. Sales promotion and service quality simultaneously have a significant influence on customer repurchase intention.